Utilization and likelihood of radiologic diagnostic imaging in patients with implantable cardiac defibrillators. Issue 1 (27th June 2015) - Nazarian, Saman; Reynolds, Matthew R.; Ryan, Michael P.; Wolff, Steven D.; Mollenkopf, Sarah A.; Turakhia, Mintu P.
Abstract : Purpose: To examine imaging utilization in a matched cohort of patients with and without implantable cardioverter defibrillators (ICD) and to project magnetic resonance imaging (MRI) utilization over a 10‐year period. Materials and Methods: The Truven Health MarketScan Commercial claims and Medicare Supplemental health insurance claims data were used to identify patients with continuous health plan enrollment in 2009–2012. Patients with ICDs were identified using ICD‐9 and CPT codes, and matched to patients with the same demographic and comorbidity profile, but no record of device implantation. Diagnostic imaging utilization was compared across the matched cohorts, in total, by imaging categories, and in subpopulations of stroke, back pain, and joint pain. MRI use in the nonimplant group over the 4‐year period was extrapolated out to 10 years for ICD‐indicated patients. Results: A cohort of 18, 770 matched patients were identified; average age 65.5 ± 13.38 and 21.9% female. ICD patients had significantly less MRI imaging (0.23 0.70 SD vs. 0.00 0.08 SD, P < 0.0001) than nonimplant patients. Among patients with records of stroke/transient ischemic attack (TIA) (ICD 5%, nonimplant 4%) and accompanying diagnostic imaging, 44% of nonimplant patients underwent MRI vs. 1% of ICD patients ( P < 0.0001). Forecast models estimated that 53% to 64% of ICD‐eligible patients may require an MRI within 10 years. Conclusion: MRI utilization is lower in ICD patients compared to nonimplant patients, yet the burden of incident stroke/TIA, back, and joint pain suggests an unmet need for MR‐conditional devices. J. MAGN. RESON. IMAGING 2016;43:115–127.